Eco-Literacy and Climate Action in Primary School Curriculum in Kenya: EDUCATION - Gichuru, Tirus M. (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Abstract It is imperative for the 21st century schools to create graduates who are deeply connected, responsible and knowledgeable on climate matters. Whereas United Nation’s Sustainable Development Goals (SGDS) intends to limit climate change, the role of children in achieving the desired outcome remains indeterminate. Children must also understand how nature works as a system. By embedding eco-literacy in educational framework, it subsequently cultivates a generation of persons who appreciates how nature works. It also equips learners with relevant knowledge, skills, attitudes and values that cares for our planet in a sustainable manner. The Kenyan government has been implementing a policy of free and compulsory basic education for all children guided by the principle of universal access to education for every child, as enshrined in article 53, 1(b) of the constitution of Kenya of 2010. The policy creates a coveted opportunity for every child in Kenya to be eco-literate. The purpose of the study was to examine the curriculum designs for pre-primary and lower primary Education in Kenya promotes ecological and environmental literacy. The study also intended to examine how numerous players in education sector contribute to climate action. Therefore, this paper discusses the role of eco-literacy in nurturing the young generation towards climate action. It underpins the role of children by evaluating numerous learning areas on environment that are entrenched in the curriculum designs. It also discusses the roles of strategic educational players in nurturing an environment-friendly learner. Descriptive design was employed in the study. Secondary data was collected from curriculum designs for pre-primary and lower primary school, analyzed and then discussed. The paper concludes that creating an eco-literate young generation through the school curriculum is the most potent and sustainable way of mitigating the impact of climate change, now and in future. Also, curriculum designs has mainstreamed greatly promoted eco-literacy among children in Kenya.